A polyvinyl alcohol composite material and preparation method thereof
By introducing acidified modified carbon nanotubes and quaternary ammonium modified montmorillonite into polyvinyl alcohol, the problem of insufficient electromagnetic shielding and flame retardant properties of polyvinyl alcohol composite materials is solved, and efficient electromagnetic shielding and resistance of the material is achieved Improved combustion performance and is suitable for electronic equipment.
Patent Information
- Application Number
- CN202211666966.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-22
AI Technical Summary
The electromagnetic shielding and flame retardant properties of existing polyvinyl alcohol composite materials are insufficient, which limits their application in the field of electronic equipment.
Acidified modified carbon nanotubes and quaternary ammonium salt modified montmorillonite are used as modifiers, and combined with polyvinyl alcohol through specific preparation methods to form acidified modified carbon nanotubes/quaternary ammonium salt modified montmorillonite. The dispersion liquid improves the electromagnetic shielding and flame retardant properties of the material.
It significantly improves the electromagnetic shielding efficiency and flame retardant properties of polyvinyl alcohol composite materials, and is suitable for electronic equipment fields.
Smart Images

Figure CN116120685B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and particularly relates to a polyvinyl alcohol composite material and a preparation method thereof. Background Art
[0002] Sensitive components in electronic devices can be damaged by transient overvoltage caused by radiation, and non-metallic components of power systems can also cause system failure due to radiation, so it is particularly important to do a good job of electromagnetic protection for electronic components. Polyvinyl alcohol (PVA) has good biocompatibility and can be decomposed into carbon dioxide, water and some other low-molecular compounds by microorganisms in nature after use. It does not pollute the environment and is an ideal green polymer. However, its poor heat resistance, flammability and poor electromagnetic shielding performance limit its application in some fields.
[0003] At present, most of the research focuses on improving the thermal properties, mechanical properties and water resistance of polyvinyl alcohol composites, but few studies have reported on how to improve the electromagnetic shielding and flame retardant properties of polyvinyl alcohol and apply polyvinyl alcohol composites to the field of electronic equipment.
[0004] Therefore, how to improve the electromagnetic shielding performance and flame retardant performance of polyvinyl alcohol so as to make it suitable for use in electronic devices is a technical problem that those skilled in the art need to solve urgently. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present invention provides a polyvinyl alcohol composite material, wherein the components of the polyvinyl alcohol composite material include, by mass fraction: 90%-95% polyvinyl alcohol; 1%-10% acid-modified carbon nanotubes; and 1%-5% quaternary ammonium salt-modified montmorillonite.
[0006] In the first aspect, the acid-modified carbon nanotubes are obtained by: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring, heating the dispersion to 100° C. and reacting for 2 hours; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain acid-modified carbon nanotubes.
[0007] In the first aspect, in the mixed solution, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
[0008] In the first aspect, the quaternary ammonium salt modified montmorillonite is obtained by the following method: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85°C, stirring thoroughly and condensing and refluxing for 2-4h to obtain a uniform suspension; ultrasonicating the suspension to make the suspension uniformly dispersed, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain a quaternary ammonium salt modified montmorillonite.
[0009] In a second aspect, the present application provides a method for preparing a polyvinyl alcohol composite material, the preparation method comprising the following steps: preparing modified carbon nanotubes; preparing modified montmorillonite; weighing the components according to the material formula, including the following mass percentages: 90%-95% polyvinyl alcohol, 1%-10% modified carbon nanotubes and 1%-5% modified montmorillonite; mixing the modified carbon nanotubes and the modified montmorillonite, adding deionized water, and ultrasonically vibrating at 50-55°C for 30 minutes; n, obtain a dispersion of modified carbon nanotubes / modified montmorillonite; put polyvinyl alcohol into a three-necked flask, add deionized water, put it into a water bath, stir and heat to 90-100° C., and stir it magnetically for 1 hour until the polyvinyl alcohol particles are completely dissolved; add the dispersion of modified carbon nanotubes / modified montmorillonite into the three-necked flask, continue heating and stirring for 2-3 hours to form a uniform and transparent viscous liquid; let the viscous liquid flow on a glass dish to form a film, dry it naturally at room temperature, and after the coating on the glass slide is cured, move the glass dish into a vacuum drying oven and dry it at 80° C. for 4 hours to obtain a polyvinyl alcohol composite material.
[0010] In the second aspect, the modified carbon nanotubes are acid-modified carbon nanotubes.
[0011] In the second aspect, the preparation of the acid-modified carbon nanotubes includes: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring, heating the dispersion to 100° C. and reacting for 2 hours; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes.
[0012] In the second aspect, in the mixed solution, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
[0013] In the second aspect, the modified montmorillonite is quaternary ammonium salt modified montmorillonite.
[0014] In the second aspect, the preparation of the quaternary ammonium salt modified montmorillonite includes: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85°C, stirring thoroughly and condensing and refluxing for 2-4h to obtain a uniform suspension; ultrasonicating the suspension to disperse the suspension uniformly, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain a quaternary ammonium salt modified montmorillonite.
[0015] Beneficial effects: The present invention proposes a polyvinyl alcohol composite material, which is composed of 90%-95% polyvinyl alcohol by mass, 1%-10% acid-modified carbon nanotubes, and 1%-5% quaternary ammonium salt-modified montmorillonite. The present invention selects modified carbon nanotubes and montmorillonite as modifiers, which have good compatibility with the substrate. The acid-modified carbon nanotubes can effectively improve the interfacial force between the carbon nanotubes and the resin matrix. The hollow structure of the carbon nanotubes can increase the dissipation path of electromagnetic waves, enhance the interfacial polarization effect, and improve the electromagnetic shielding performance of the polyvinyl alcohol material; the quaternary ammonium salt-modified montmorillonite is a silicate material with a multilayer structure, which has a good barrier effect and plays a certain heat insulation role, greatly improving the flame retardancy of the polyvinyl alcohol material. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of this specification or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 is a flow chart of a method for preparing a polyvinyl alcohol composite material according to an embodiment of the present invention; DETAILED DESCRIPTION
[0018] The technical scheme of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0019] Meanwhile, throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0020] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0021] It should be noted that the symbol “ / ” between the two materials involved in the present invention means “and”, for example, “modified carbon nanotubes / modified montmorillonite” means “modified carbon nanotubes and modified montmorillonite”.
[0022] Example 1
[0023] The polyvinyl alcohol composite material was obtained by the following method:
[0024] (1) According to the material formula, the following components are included in mass percentage: polyvinyl alcohol 90%, acid-modified carbon nanotubes 8%, and quaternary ammonium salt-modified montmorillonite 2%; each component is accurately weighed;
[0025] The acid-modified carbon nanotubes are obtained by the following method: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, and obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring; in the mixture, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; heating the dispersion to 100° C. and reacting for 2 h; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes; the quaternary ammonium salt-modified montmorillonite is obtained by The method is as follows: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., stirring thoroughly and condensing and refluxing for 2-4 hours to obtain a uniform suspension; subjecting the suspension to ultrasonication to uniform dispersion, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain a quaternary ammonium salt-modified montmorillonite;
[0026] (2) mixing the acid-modified carbon nanotubes and the quaternary ammonium salt-modified montmorillonite, adding 50 mL of deionized water, and ultrasonically shaking at 50-55° C. for 30 min to obtain a dispersion of modified carbon nanotubes / modified montmorillonite;
[0027] (3) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0028] (4) adding the modified carbon nanotube / modified montmorillonite dispersion into the three-necked flask, and continuing to heat and stir for 2-3 hours to form a uniform, transparent, viscous liquid;
[0029] (5) The viscous liquid is allowed to flow onto a glass dish to form a film, which is then naturally air-dried at room temperature. After the film on the glass slide is solidified to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80° C. for 4 h to obtain a polyvinyl alcohol composite material.
[0030] Example 2
[0031] The polyvinyl alcohol composite material was obtained by the following method:
[0032] (1) According to the material formula, the following components are included in mass percentage: 90% polyvinyl alcohol, 7.5% acid-modified carbon nanotubes, and 2.5% quaternary ammonium salt-modified montmorillonite; each component is accurately weighed;
[0033] The acid-modified carbon nanotubes are obtained by the following method: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, and obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring; in the mixture, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; heating the dispersion to 100° C. and reacting for 2 h; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes; the quaternary ammonium salt-modified montmorillonite is obtained by The method is as follows: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., stirring thoroughly and condensing and refluxing for 2-4 hours to obtain a uniform suspension; subjecting the suspension to ultrasonication to uniform dispersion, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain a quaternary ammonium salt-modified montmorillonite;
[0034] (2) mixing the acid-modified carbon nanotubes and the quaternary ammonium salt-modified montmorillonite, adding 50 mL of deionized water, and ultrasonically shaking at 50-55° C. for 30 min to obtain a dispersion of modified carbon nanotubes / modified montmorillonite;
[0035] (3) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0036] (4) adding the modified carbon nanotube / modified montmorillonite dispersion into the three-necked flask, and continuing to heat and stir for 2-3 hours to form a uniform, transparent, viscous liquid;
[0037] (5) The viscous liquid is allowed to flow onto a glass dish to form a film, which is then naturally air-dried at room temperature. After the film on the glass slide is solidified to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80° C. for 4 h to obtain a polyvinyl alcohol composite material.
[0038] Example 3
[0039] The polyvinyl alcohol composite material was obtained by the following method:
[0040] (1) According to the material formula, the following components are included in mass percentage: polyvinyl alcohol 90%, acid-modified carbon nanotubes 5%, and quaternary ammonium salt-modified montmorillonite 5%; each component is accurately weighed;
[0041] The acid-modified carbon nanotubes are obtained by the following method: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, and obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring; in the mixture, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; heating the dispersion to 100° C. and reacting for 2 h; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes; the quaternary ammonium salt-modified montmorillonite is obtained by The method is as follows: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., stirring thoroughly and condensing and refluxing for 2-4 hours to obtain a uniform suspension; subjecting the suspension to ultrasonication to uniform dispersion, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain a quaternary ammonium salt-modified montmorillonite;
[0042] (2) mixing the acid-modified carbon nanotubes and the quaternary ammonium salt-modified montmorillonite, adding 50 mL of deionized water, and ultrasonically shaking at 50-55° C. for 30 min to obtain a dispersion of modified carbon nanotubes / modified montmorillonite;
[0043] (3) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0044] (4) adding the modified carbon nanotube / modified montmorillonite dispersion into the three-necked flask, and continuing to heat and stir for 2-3 hours to form a uniform, transparent, viscous liquid;
[0045] (5) The viscous liquid is allowed to flow onto a glass dish to form a film, which is then naturally air-dried at room temperature. After the film on the glass slide is solidified to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80° C. for 4 h to obtain a polyvinyl alcohol composite material.
[0046] The above Examples 1-3 can prepare polyvinyl alcohol composite materials. In order to further reflect the creativity of the present invention, the present invention uses the following Comparative Examples 1-3 to form a control test with Examples 1-3.
[0047] Comparative Example 1
[0048] The polyvinyl alcohol material was obtained as follows:
[0049] (1) According to the material formula, accurately weigh 100% of polyvinyl alcohol with a mass percentage of 100%;
[0050] (2) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0051] (3) Continue heating and stirring for 2-3 hours;
[0052] (4) The film is formed by drooling on a glass dish and naturally air-dried at room temperature. After the coating on the glass slide is solidified to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80°C for 4 hours to obtain a polyvinyl alcohol material.
[0053] Comparative Example 2
[0054] The polyvinyl alcohol material was obtained as follows:
[0055] (1) According to the material formula, the following components are included in mass percentage: polyvinyl alcohol 90%, acid-modified carbon nanotubes 10%; each component is accurately weighed;
[0056] The acid-modified carbon nanotubes are obtained by the following method: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, and obtaining a dispersion with a concentration of 2-5 g / 100 mL after magnetic stirring; in the mixture, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1; heating the dispersion to 100° C. and reacting for 2 hours; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes;
[0057] (2) adding 50 mL of deionized water to the acidified modified carbon nanotubes, and ultrasonically shaking at 50-55° C. for 30 min to obtain a dispersion of the modified carbon nanotubes;
[0058] (3) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0059] (4) adding the dispersion of modified carbon nanotubes into the three-necked flask, and continuing to heat and stir for 2-3 hours to form a uniform, transparent, viscous liquid;
[0060] (5) The viscous liquid is allowed to flow onto a glass dish to form a film, which is then naturally air-dried at room temperature. After the film on the glass slide solidifies to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80° C. for 4 h to obtain a polyvinyl alcohol material.
[0061] Comparative Example 3
[0062] The polyvinyl alcohol material was obtained as follows:
[0063] (1) According to the material formula, the following components are included in mass percentage: polyvinyl alcohol 90%, quaternary ammonium salt modified montmorillonite 10%; accurately weigh each component;
[0064] The quaternary ammonium salt modified montmorillonite is obtained by the following method: adding montmorillonite powder to deionized water, stirring thoroughly to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., stirring thoroughly and condensing and refluxing for 2-4 hours to obtain a uniform suspension; subjecting the suspension to ultrasonication to uniform dispersion of the suspension, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain the quaternary ammonium salt modified montmorillonite;
[0065] (2) adding 50 mL of deionized water to the quaternary ammonium salt-modified montmorillonite, and ultrasonically vibrating at 50-55° C. for 30 min to obtain a dispersion of the modified montmorillonite;
[0066] (3) PVA was placed in a 250 mL three-necked flask, 100 mL of deionized water was added, the mixture was placed in a water bath, stirred and heated to 90-100° C., and magnetically stirred for 1 h until the PVA particles were completely dissolved;
[0067] (4) adding the modified montmorillonite dispersion into the three-necked flask, and continuing to heat and stir for 2-3 hours to form a uniform, transparent, viscous liquid;
[0068] (5) The viscous liquid is allowed to flow onto a glass dish to form a film, which is then naturally air-dried at room temperature. After the film on the glass slide is solidified to a certain extent, the glass dish is moved into a vacuum drying oven and dried at 80° C. for 4 h to obtain a polyvinyl alcohol composite material.
[0069] Effect Example
[0070] The materials prepared in Examples 1-3 and Comparative Examples 1-3 were tested for performance, and the test results are shown in Table 1.
[0071] Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Electromagnetic shielding effectiveness / dB 35.6 36.8 34.7 19.5 25.8 24.6 UL94 flame retardant V0 V0 V0 HB V1 V1
[0072] Table 1 Material performance test results of Examples 1-3 and Comparative Examples 1-3
[0073] As shown in Table 1, the flame retardant properties and electromagnetic shielding properties of the polyvinyl alcohol composite material developed by compounding polyvinyl alcohol, acid modified carbon nanotubes and quaternary ammonium salt modified montmorillonite in different proportions in Examples 1-3 of the present invention are excellent. The acid modified carbon nanotubes are evenly dispersed in the polyvinyl alcohol matrix, and a good spatial conductive network is formed by winding and interlacing, which can increase the dissipation path of electromagnetic waves, enhance the interfacial polarization effect, effectively improve the electromagnetic wave loss capacity, and enable the polyvinyl alcohol composite material to obtain a higher electromagnetic shielding effectiveness; the organic cations in the quaternary ammonium salt surfactant replace the original hydrated cations between the montmorillonite layers through ion exchange, so that the montmorillonite has better properties such as lipophilicity, organic compatibility and thermal stability, effectively opens the interlayer spacing of montmorillonite and improves the compatibility of montmorillonite with organic matter. The interlamellar spacing of silicate increases, and when melt extrusion is performed, the polymer chain in the molten state is more likely to enter between the lamellae. The silicate lamellae cover the surface of the material, play a heat insulation role, and effectively improve the flame retardant properties of the polyvinyl alcohol material.
[0074] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0075] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0076] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A polyvinyl alcohol composite material, characterized in that: The components of the polyvinyl alcohol composite material include, by mass fraction: Polyvinyl alcohol 90%-95%; acid modified carbon nanotubes 1%-10%; quaternary ammonium salt modified montmorillonite 1%-5%; The acid modified carbon nanotubes are obtained by: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, stirring with a magnetic force to obtain a dispersion with a concentration of 2-5 g / 100 mL, heating the dispersion to 100° C. and reacting for 2 hours; cooling after the reaction, washing with distilled water until the solution has a pH of 7-8, filtering, drying, and grinding to obtain the acid modified carbon nanotubes; The quaternary ammonium salt modified montmorillonite is obtained by the following method: adding montmorillonite powder to deionized water, stirring fully to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., stirring fully and condensing and refluxing for 2-4 hours to obtain a uniform suspension; subjecting the suspension to ultrasonication to uniform dispersion of the suspension, then centrifuging to remove the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain the quaternary ammonium salt modified montmorillonite.
2. The polyvinyl alcohol composite material according to claim 1, characterized in that: In the mixed solution, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:
1.
3. A method for preparing a polyvinyl alcohol composite material, characterized in that: The preparation method comprises the following steps: preparing modified carbon nanotubes; preparing modified montmorillonite; According to the material formula, the following components are included in mass percentage: polyvinyl alcohol 90%-95%, modified carbon nanotubes 1%-10% and modified montmorillonite 1%-5%, and each component is weighed; After the modified carbon nanotubes and the modified montmorillonite are mixed, deionized water is added, and ultrasonic vibration is performed at 50-55° C. for 30 minutes to obtain a dispersion of the modified carbon nanotubes / modified montmorillonite; Put polyvinyl alcohol into a three-necked flask, add deionized water, put it in a water bath, stir and heat to 90-100°C, and stir magnetically for 1 hour until the polyvinyl alcohol particles are completely dissolved; Add the modified carbon nanotube / modified montmorillonite dispersion into the three-necked flask, continue heating and stirring for 2-3 hours, and form a uniform, transparent, viscous liquid; The viscous liquid was drooled on the glass dish to form a film, and the film was naturally air-dried at room temperature. After the film on the glass slide was solidified, the glass dish was moved into a vacuum drying oven and dried at a temperature of 80° C. for 4 hours to obtain a polyvinyl alcohol composite material; The modified carbon nanotubes are acid-modified carbon nanotubes; The modified montmorillonite is quaternary ammonium salt modified montmorillonite; The preparation of the acid-modified carbon nanotubes includes: adding carbon nanotubes to a mixture of concentrated sulfuric acid and concentrated nitric acid, magnetically stirring to obtain a dispersion with a concentration of 2-5 g / 100 mL, heating the dispersion to 100° C. and reacting for 2 hours; cooling after the reaction, washing with distilled water until the solution pH is 7-8, filtering, drying, and grinding to obtain the acid-modified carbon nanotubes; The preparation of the quaternary ammonium salt modified montmorillonite comprises: adding montmorillonite powder to deionized water, fully stirring to obtain a dispersion with a concentration of 30-60 g / L, adding an ester-containing quaternary ammonium salt surfactant to the dispersion, heating to 70-85° C., fully stirring and condensing and refluxing for 2-4 hours to obtain a uniform suspension; ultrasonicating the suspension to make the suspension uniformly dispersed, then centrifugally separating and removing the supernatant to obtain a precipitate, washing, drying and grinding the precipitate to obtain the quaternary ammonium salt modified montmorillonite.
4. The method for preparing the polyvinyl alcohol composite material according to claim 3, characterized in that: In the mixed solution, the volume ratio of concentrated sulfuric acid to concentrated nitric acid is 3:1.
Citation Information
Cited By
A preparation method of modified polyvinyl alcohol adhesive
CN119736039A
A preparation method of modified polyvinyl alcohol adhesive
CN119736039B
